Processing of coconut sap into syrup and granular sugar using different evaporation techniques for economical production - Tuseef, Asghar Muhammad (2021)
Malaysia is the 6th major raw sugar importing country, to support domestic consumption. Producing sugar from coconut sap is an alternative to sugarcane; in fact, coconut sugar has entered the global marketplace with increasing consumption by a more health-conscious world population. In Malaysia, coconut sugar has limited use, primarily as an ingredient in traditional dishes. Commercial production of coconut sugar by open-heat evaporation exposes the sap to a high temperature (>100 °C) for a long time (3-5 hours), causing inconsistent and decreased quality of the coconut sugar produced. The overall objective of this research was to explore the use of coconut sap as an alternative sugar source by identifying a suitable processing method that can efficiently produce a high-quality product with the potential for commercialization. Initially, fresh coconut sap, sugar palm sap, and sugarcane juice were analyzed and compared their properties and nutrient values. The concentrations of three sugars (fructose, glucose, and sucrose), six vitamins (vitamin C, B1, B3, B4, B2, and B10), and antioxidant activities were higher in coconut sap compared with the other two (2) sugar sources. Then, three evaporative processing methods [rotary (RE), microwave (ME), and open-heat (OHE) evaporation] with different conditions were used to produce coconut sugar. Rotary evaporation at 60 °C and 250 mbar vacuum pressure (RE-60) provided the suitable conditions, producing coconut sugar after a short processing time (12.2 min) at a lower processing temperature (54.8 °C), which contributed to lower energy requirements (0.35kWh). Storage stability of the coconut sugar was evaluated at room temperature (25 °C) and elevated temperature (38 °C) for 8 weeks. Less change in moisture content, water activity, stickiness, lightness, colour, and browning index was observed for RE coconut sugar compared with those made using the other processing methods, suggesting greater quality stability of RE sugar. Morphology changes of sugar stored at elevated temperature compared with room temperature supported that room temperature is more appropriate for coconut sugar storage, and temperature excursions during shipping and warehousing should be avoided. Sensory evaluation showed higher scores for all attributes for RE compared with OHE sugar. The design, scale-up simulation, and cost analysis for commercial production of coconut sugar were also evaluated. The RE method was more time-efficient and economical compared with the ME and OHE methods. Production costs and pay-back period were more favourable, with a higher gross margin for coconut sugar produced with RE-60. Coconut sugar production based on a minimum capacity of 750L/batch (2250L/day) can be a viable project in the Sabak Bernam district of Selangor state Malaysia. The coconut sugar price calculated for this project (RM35.76/kg) lower compared with commercially available coconut sugar price (RM45/kg) and the project is expected to payback invested capital in about 3.50 years. The project could generate local employment by producing sugar from local materials and could have an impact on foreign exchange by decreasing the sugar import price. Overall, the study showed that coconut sap processed using RE can be an economical source of high-quality granular sugar. Rotary evaporation at 60 °C provided more suitable processing conditions, with minimal energy requirement. The production of marketable coconut sugar has the potential to supplement both local and international demand, generating additional income. Strategies to address the well-defined constraints and limitations of scale-up and commercialization are needed, and further research is warranted.